Compact Optical Polarization‐Insensitive Zoom Metalens Doublet. Issue 13 (4th May 2020) - Wei, Yunxuan; Wang, Yuxi; Feng, Xing; Xiao, Shunyuan; Wang, Zhaokun; Hu, Tie; Hu, Manchen; Song, Jinwen; Wegener, Martin; Zhao, Ming; Xia, Jinsong; Yang, Zhenyu
Abstract: Metasurface‐based lenses (metalenses) offer specific conceptual advantages compared to ordinary refractive lenses. For example, it is possible to tune the focal length of a metalens doublet by varying the relative angle between the two metalenses while fixing their distance, leading to an extremely compact zoom lens. An improved polarization‐insensitive design based on silicon nanocylinders on silica substrates is presented. This design is realized and characterized experimentally at 1550 nm wavelength. By varying the relative angle between the metalenses in steps of 10°, tuning of the doublet focal length is demonstrated from −54 mm to ±3 mm to +54 mm. This results in a zoom factor of an imaging system varying between 1 and 18. For positive focal lengths, the doublet focusing efficiency has a minimum of 34% and a maximum of 83%. Experiment and theory are in very good agreement. Abstract : In this work, experimental results following an optimized design of a zoom metalens doublet are presented, based on rotating two metasurfaces with respect to each other at fixed distance between them, at an operation wavelength of 1550 nm. The focal length could be adjusted from ±3 mm to ±54 mm, corresponding to extremal zoom factors of ±18× at an average focusing efficiency of 54%.